2018
DOI: 10.1007/s00592-018-1158-3
|View full text |Cite
|
Sign up to set email alerts
|

Salivary anti-coxsackievirus-B4 neutralizing activity and pattern of immune parameters in patients with type 1 diabetes: a pilot study

Abstract: The association between saliva anti-CV-B4 activity and disturbance of immune system in T1D patients deserves further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The presence of enteroviruses in the gut can result in specific IgA antibodies in both the intestinal mucosa and saliva, as all inducer and effector sites of the mucosa-associated lymphoid tissue are functionally interconnected 56 . For example, in studies from several countries (France, Republic of the Congo, Lebanon and Benin), high titres of neutralizing IgA1 anti-CVB4 antibodies were detected in the saliva more often in patients with T1DM than in control individuals 57 , 58 . Interestingly, this salivary anti-CVB4 activity was maintained throughout a 4-year follow-up period in patients with T1DM but not in control individuals 57 .…”
Section: Enterovirus Persistence In T1dmmentioning
confidence: 99%
“…The presence of enteroviruses in the gut can result in specific IgA antibodies in both the intestinal mucosa and saliva, as all inducer and effector sites of the mucosa-associated lymphoid tissue are functionally interconnected 56 . For example, in studies from several countries (France, Republic of the Congo, Lebanon and Benin), high titres of neutralizing IgA1 anti-CVB4 antibodies were detected in the saliva more often in patients with T1DM than in control individuals 57 , 58 . Interestingly, this salivary anti-CVB4 activity was maintained throughout a 4-year follow-up period in patients with T1DM but not in control individuals 57 .…”
Section: Enterovirus Persistence In T1dmmentioning
confidence: 99%
“…The study process is shown in Figure 1. Among 1501 potentially relevant studies, 38 met the inclusion criteria (10,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58). The dataset included 5921 subjects (2841 T1D patients and 2841 controls).…”
Section: Characteristics Of the Studies Included In The Meta-analysismentioning
confidence: 99%
“…A meta-analysis identified the correlation between enterovirus infection and T1D in 2011 (17). Although several original studies have been reported from 2012 to 2020 (10,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), no updated meta-analysis has been performed to explore and refine the correlation. The conclusions of the original studies are conflicting, and thus, a meta-analysis including the latest studies is still needed to evaluate the association between enterovirus infection and T1D.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these findings indicate that the activity of salivary anti-Coxsackievirus B4 in T1DM patients is associated with immune system dysregulation. Thus, the anti-Coxsackievirus B4 activity in the saliva can be used as a non-invasive marker to examine the viral pathogenesis of T1DM, especially in high-risk populations [ 41 ].…”
Section: Africamentioning
confidence: 99%